2009
DOI: 10.1016/j.biopsycho.2009.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Auditory stream segregation in children with Asperger syndrome

Abstract: Individuals with Asperger syndrome (AS) often have difficulties in perceiving speech in noisy environments. The present study investigated whether this might be explained by deficient auditory stream segregation ability, that is, by a more basic difficulty in separating simultaneous sound sources from each other. To this end, auditory event-related brain potentials were recorded from a group of school-aged children with AS and a group of age-matched controls using a paradigm specifically developed for studying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 31 publications
(40 reference statements)
3
44
0
Order By: Relevance
“…However, in two other electrophysiological studies intensity processing of pure tones was deficient (Bruneau et al, 1999(Bruneau et al, , 2003. These different outcomes could probably be explained by differences in participant selection: Bruneau et al (1999) and Bruneau et al (2003) studied a group of very young mentally retarded children with autism, whereas the other studies either tested a group of children with Asperger syndrome (Lepistö et al, 2009) or a group of children with autism or ASD with mixed IQs (Khalfa et al, 2004;Jones et al, 2009).…”
Section: Pure Tone Processingmentioning
confidence: 98%
See 3 more Smart Citations
“…However, in two other electrophysiological studies intensity processing of pure tones was deficient (Bruneau et al, 1999(Bruneau et al, , 2003. These different outcomes could probably be explained by differences in participant selection: Bruneau et al (1999) and Bruneau et al (2003) studied a group of very young mentally retarded children with autism, whereas the other studies either tested a group of children with Asperger syndrome (Lepistö et al, 2009) or a group of children with autism or ASD with mixed IQs (Khalfa et al, 2004;Jones et al, 2009).…”
Section: Pure Tone Processingmentioning
confidence: 98%
“…One behavioural study found enhanced intensity perception (Khalfa et al, 2004) and one study found intact, but not enhanced, intensity discrimination of pure tones (Jones et al, 2009). Electrophysiological intensity processing of pure tones was intact in one study when stream segregation was not required (Lepistö et al, 2009). However, in two other electrophysiological studies intensity processing of pure tones was deficient (Bruneau et al, 1999(Bruneau et al, , 2003.…”
Section: Pure Tone Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that previous research shows that people with ASD have increased sensitivity (Frith and Baron-Cohen, 1987) and reduced tolerance (hyperacusis) (Khalfa et al, 2004;Rosenhall et al, 1999) to loudness, intensity discrimination ability appears to be intact in adults and adolescents with ASD (Bonnel et al, 2010;. Of note, one study used pure tones of varying intensities (the 'oddball' paradigm) to investigate auditory stream segregation (mismatch negativity (MMN) responses) in children with ASD (Lepistö et al, 2009). Intensity discrimination was intact in ASD when stream segregation (to separate sounds that come from different sources) was not required.…”
mentioning
confidence: 99%